PENGARUH TINDAKAN ISAP LENDIR TERHADAP PERUBAHAN SATURASI O2 PADA PASIEN DENGAN PENURUNAN KESADARAN DI RUANG ICU RSUD WONOSOBO - Wanidi, Sri; Al Ummah, Basirun; Santoso, Dadi (Jurnal Ilmiah Kesehatan Keperawatan, 2014)
Patient's airway clearance can be done to improve oxygenation that needed by the body. Suction of mucus in respiratory tract is done through the nose, mouth and trachea (tracheotomy patients). Management of suction for patients in intensive care unit influences the oxygen need compliance. The study aims to determine the influence of mucus suction to the O2 saturation change of patients with consciousness impairment in ICU of Wonosobo Regional Hospital. This is a pre-experimental / quasi experiment research which means that the researcher only held a one-time treatment which has considerably had influences. The study was conducted by using a paired t test trial. The samples consist of 37 respondents taken by using total sampling. Independent variable is the exploitation of mucus, while the dependent variable is oxygen saturation. Research results show the influence of the long suction mucus oxygen saturation in patients with consciousness impairment with p value 0.014 < 0.05. There is a comparison of oxygen saturation values ​​before and after the mucus suction in patients with consciousness impairment. it is suggested to the nurse to provide mucus suction for patients with impaired oxygenation and it should not exceed 15 seconds.   Keywords      : Mucus suction, oxygen saturation.